Cold shock in Bacillus subtilis: different effects of benzyl alcohol and ethanol on the membrane organisation and cell adaptation - Konopásek, I; Strzalka, K; Svobodová, J (Biochimica et biophysica acta, 2000)
A temperature shift-down of Bacillus subtilis from 40 to 20 degrees C induces an 80 min growth lag. Benzyl alcohol reduced this period to 51 min, whereas ethanol prolonged it up to 102 min. The effect of the two alcohols on the membrane state was investigated by measuring the steady-state fluorescence anisotropy and analysing the lifetime distribution of diphenylhexatriene (DPH) and its polar derivative, TMA-DPH. As followed from the fluorescence anisotropy, the two alcohols exerted similar (fluidizing) effects on the cytoplasmic membranes of B. subtilis. However, benzyl alcohol significantly shortened the main DPH lifetime component and widened its distribution, while ethanol had no effect. The benzyl alcohol activity was interpreted in terms of an increased membrane hydration due to disordering of the membrane structure. Such an effect imitates the cold shock induced synthesis of unsaturated fatty acids in B. subtilis. The fatty acid analysis revealed that ethanol hindered this adaptive synthesis of fatty acids. At the same time, its effect on the membrane state (membrane order) was very low and could not substitute the physiological response as was the case with benzyl alcohol. It can thus be concluded that the adaptation of the membrane physical state contributes significantly to the cold shock response of B. subtilis.
Keywords: poločas; intracelulární membrány; Fatty Acids, Unsaturated; Bacillus subtilis; nenasycené mastné kyseliny; Adaptation, Physiological; nízká teplota; ethanol; Half-Life; difenylhexatrien; Cold Temperature; Intracellular Membranes; anizotropie; fluorescenční barviva; Fluorescent Dyes; Benzyl Alcohol; Cytoplasm; fyziologická adaptace; cytoplazma; benzylalkohol; Diphenylhexatriene; Ethanol; Anisotropy